Anne of Avonlea - Montgomery, L.M. 1874-1942.; Parry, Caroline (New York Dell Laurel-Leaf, 2003)
In this sequel to "Anne of Green Gables," teenage Anne Shirley becomes a schoolteacher in a small village on Prince Edward Island.
"Special Collector's Edition" -- Front cover.
Age 10 and up.
Keywords: Orphans -- Fiction; Teachers -- Fiction; Islands -- Fiction; Prince Edward Island -- Fiction